The Role of Entrepreneurship Education in Forming an Entrepreneurial Ecosystem: A Systematic Literature Review - zutiasari, Ika; Aulia Martha, Jefri; Muaddab, Hafis; Ayu Anindya, Anastasia (Universitas Negeri Semarang, 2024)
Entrepreneurship education faces various problems that hinder the creation of a strong and sustainable entrepreneurial ecosystem. So, this research seeks to fill the gap in the literature by studying the direct effect of perceived entrepreneurial ecosystem factors and how the existence of entrepreneurship education in creating a good entrepreneurial ecosystem through systematic literature review analysis and compiled with PRISMA guidelines. Based on this method, the research obtained fourteen articles that fit the subject criteria for further analysis. According to the results of the analysis of the role of entrepreneurship education on the Entrepreneurial Ecosystem is that overall, entrepreneurship education plays a key role in shaping the entrepreneurial ecosystem by helping to produce quality entrepreneurs, encouraging innovation, building networks and collaboration, teaching business skills, encouraging entrepreneurial attitudes, and providing support and guidance to aspiring entrepreneurs. This is supported by several actions that can be taken including adjustment and relevance of education to students, developing a student-centered entrepreneurship education model, paying attention to cooperation with faculties, universities, government, and industry to get adequate facilities and access to develop entrepreneurship education better again so that the entrepreneurship ecosystem can also be achieved well